APPLICATION OF THE PICTURE AND PICTURE METHOD TO IMPROVE STUDENTS’ MOTIVATION AND ACHIEVEMENT IN WRITING NARRATIVE ARTICLES - Raudatul Izmi Lubis; Arini Vika Sari; Sarwandi (Journal of Islamic, Social, Economics and Development, 2023)
Language is also interpreted as learning which contains procedures for communicating. In learning, language is divided into several parts, one of which is writing skills, writing skills are very important to be trained and applied, especially in writing narrative essays. Narrative essay is an essay that explains an event based on the time sequence of events and chronological events. In writing narrative essays the method used is Picture and Picture. The Picture and Picture method is a method that displays material about images combined with media. The form of this research is Classroom Action Research, which consists of two cycles. Data collection techniques used are in the form of Observations, Tests and Documentation. The research subjects were 25 class VII students of MTs Alwasliyah Pantai Labu for the 2021/2022 academic year with the aim of being able to improve their narrative essay writing skills. The average value of students in writing narrative essays has a very large difference, namely before the counseling and after the counseling. The average value of students before the counseling was 67.2 while the student's score after the counseling was 81.6. Student scores increased when applying the Picture and Picture method compared to the lecture method taught before.